The Mediating Role of Attitudes Towards Eating in the Relationship Between Compulsive Instagram Use and Orthorexia in Adults - Unal GA; Kocatepe Avcı U (Psychology Research and Behavior Management)
Gonca Ayse Unal,1 Ufuk Kocatepe Avcı2 1Clinic of Psychiatry, Mersin Sehir Egitim ve Arastirma Hastanesi, Toroslar, Mersin, Turkey; 2Department of Psychology, Çağ University, Toroslar, Mersin, TurkeyCorrespondence: Gonca Ayse Unal, Mersin Sehir Egitim ve Arastirma Hastanesi, Psychiatry Clinic, Korukent District, 96015 Street, Toroslar, Mersin, 33240, Turkey, Tel +90 3243251000, Fax +903242251010/11, Email goncaunal33@gmail.comPurpose: The purpose of this study is to examine the relationship between compulsive use of social media and orthorexia, with a focus on the mediating role of eating attitudes.Patients and Methods: The study involved 255 participants between the ages of 18– 65 who did not have any psychiatric disorders or developmental disabilities. The participants completed a Sociodemographic Information Form, Orthorexia Nervosa Inventory, Social Media Addiction Scale, and Eating Attitudes Test.Results: The results showed a positive correlation between orthorexia and all other scales and sub-scales. Multiple regression analyses revealed that eating attitudes were a significant predictor of all sub-dimensions of orthorexia. Additionally, the sub-dimension of Conflict on the Social Media Addiction Scale was found to predict the Impairments sub-dimension of orthorexia. Further analysis using the PROCESS macro showed that compulsive use of social media not only directly predicted orthorexia, but also indirectly through eating attitudes.Conclusion: These findings emphasize the importance of addressing both compulsive use of social media and eating attitudes when working with individuals who exhibit orthorexic symptoms in clinical settings.Keywords: eating attitude, Instagram, orthorexia, compulsive use of social media, adult